2015
DOI: 10.1016/j.neuroimage.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal connectivity of motor learning-related dorsal premotor cortex

Abstract: The dorsal premotor cortex (dPMC) is a key region for motor learning and sensorimotor integration, yet we have limited understanding of its functional interactions with other regions. Previous work has started to examine functional connectivity in several brain areas using resting state functional connectivity (RSFC) and meta-analytical connectivity modelling (MACM). More recently, structural covariance (SC) has also been proposed as a technique that may also allow delineation of functional connectivity. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 110 publications
(162 reference statements)
8
23
0
Order By: Relevance
“…Like the results reported by Hardwick et al [], in this study, most areas found to be activated according to the MACM were also activated in the rsFC study. We reported the peak coordinates of the areas identified in both the rsFC and MACM analyses in Supporting Information Table S3.…”
Section: Resultssupporting
confidence: 89%
“…Like the results reported by Hardwick et al [], in this study, most areas found to be activated according to the MACM were also activated in the rsFC study. We reported the peak coordinates of the areas identified in both the rsFC and MACM analyses in Supporting Information Table S3.…”
Section: Resultssupporting
confidence: 89%
“…We therefore argue that the increased PMd recruitment was beneficial, affording a more precise synchronization of the finger tapping with the regular pace provided by the visual cue. Our findings are in good agreement with previous work showing that the PMd plays a prominent role in visuomotor integration (58)(59)(60)(61)(62)(63).…”
Section: Discussionsupporting
confidence: 93%
“…The highest convergence will probably be found in the seed region, but significant convergence outside the seed indicates significant co-activation. Meta-Analytic Co-Activation Modeling (MACM) thus provides a complementary aspect of long-range integration relative to measures such as resting-state functional connectivity or structural covariance (Clos et al, 2014; Hardwick et al, 2015). …”
Section: Discussionmentioning
confidence: 99%